The behavioral intention telepharmacy questionnaire based on theory of personal health differences and planned behavior - Sulistyaningrum, Indriyati Hadi; Widodo, Teguh; Suyanto, Achmad Manshur Ali; Pribadi, Prasojo (International Journal of Public Health Science (IJPHS), 2024)
Modern pharmaceutical services are offered via telepharmacy, an internet platform. Identification of items and factors that influence people's behavioral intentions towards telepharmacy services is needed to develop this service. The study aims to develop a questionnaire based on a research model that combines two well-known theories: the theory of personal health differences (TPHD) and the theory of planned behavior (TPB) technique. The purposive sampling strategy was combined with a cross-sectional observational method. 116 participants who were at least 18 years old were given the questionnaire. Convenience sampling from various population subgroups was used to select them. Data analysis was then conducted using the exploratory factor analysis (EFA). Factors were extracted using varimax rotation and principal component analysis. The results showed that the questionnaire consists of 16 items divided into 5 constructs (attitude and self-efficacy, behavioral intention, subjective norm, personal health status, and personal health value), this study proves that the behavioral intention telepharmacy questionnaire based on personal health differences and planned behavior theory is a reliable and valid measure. It can also draw attention to the many aspects of adoption behavior, helping service providers toward the successful digitalization of pharmaceutical services by fostering telepharmacy literacy. The application of telepharmacy is both a hope and a challenge for pharmacists and society, especially in terms of the intention to provide safe and quality pharmaceutical care.